The correlation between CEO remuneration and company performance : a Singapore-Hong Kong comparison. - Chui, Vanessa Jie Yi. (2013)
This paper recognizes the quintessential role that Chief Executive Officer (CEO) remuneration historically plays in aligning the interests of the CEOs with those of the stockholders by virtue of motivating them to improve company performance. On the other hand, such pay-for-performance schemes have been increasingly facing criticism for its seemingly growing ineffectiveness. This paper strives to gain a greater understanding of how the application of these remuneration schemes has been affected, if at all, in face of such controversy. Based on a sample of 143 Singapore and Hong Kong companies in the financial year ended 2012, we examined and compared the correlation between CEO remuneration and company performance for the two countries/regions.